2016
DOI: 10.1186/s12879-016-1492-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes for patients with Middle Eastern Respiratory Syndrome Coronavirus (MERS CoV) infection at a coronavirus referral center in the Kingdom of Saudi Arabia

Abstract: BackgroundMiddle Eastern Respiratory Syndrome coronavirus (MERS-CoV) is a poorly understood disease with no known treatments. We describe the clinical features and treatment outcomes of patients with laboratory confirmed MERS-CoV at a regional referral center in the Kingdom of Saudi Arabia.MethodsIn 2014, a retrospective chart review was performed on patients with a laboratory confirmed diagnosis of MERS-CoV to determine clinical and treatment characteristics associated with death. Confounding was evaluated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
2
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 39 publications
10
144
2
11
Order By: Relevance
“…The first group survived and the latter group died [67]. The use of interferon beta, interferon alpha, and ribavirin was associated with survival rates of 78.3%, 75%, and 68.4%, respectively [66].…”
Section: Human Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The first group survived and the latter group died [67]. The use of interferon beta, interferon alpha, and ribavirin was associated with survival rates of 78.3%, 75%, and 68.4%, respectively [66].…”
Section: Human Studiesmentioning
confidence: 98%
“…One patient was treated with pegylated interferon, ribavirin and lopinavir/ritonavir and viremia was detected for two days following therapy with triple therapy [64]. In a case series, eight patients received mycophenolate mofetil and all survived [66].…”
Section: Human Studiesmentioning
confidence: 99%
“…In contrast with animal model, the combination IFN-␤1b/MMF was administered to 8 patients in Saudi Arabia. All the patients survived but had lower APACHE II scores that other patient groups [71].…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 73%
“…The health-system delay in identifying a MERS-CoV case may be attributed to the delay in the virus recognition in medical institutions [6] and to the limited awareness among healthcare-workers [11], as a survey conducted on 1216 healthcare-workers revealed that only 47.6% of the physicians and 30.4% of the nurses were aware that some infected patients had no symptoms [11]. Also diagnosis of MERS-CoV [3] and medical care for patients with MERS-CoV [12] remain major challenges in healthcare facilities. Further understanding on the causes of patient and health-system delay is needed, as it can be used as a modifiable factor to reduce diagnostic delay and to improve the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%